Change in intention and hesitancy regarding COVID-19 vaccines in a cohort of adults in Quebec during the pandemic - Maude Dionne; Louis Rochette; Denis Hamel; Ève Dube (Taylor & Francis Group, 2024)
ABSTRACTAlthough COVID-19 vaccine uptake was high in Quebec for the primary series, vaccine acceptance decreased for the subsequent booster doses. This article presents the evolution of vaccine intention, self-reported vaccination behaviors, and vaccine hesitancy over 2 years. A series of cross-sectional surveys were conducted in Quebec between March 2020 and March 2023, with a representative sample of 3,330 adults recruited biweekly via a Web panel. Panelists could have answered multiple times over the course of the project. A cohort of respondents was created to assess how attitudes and behaviors about COVID-19 vaccines evolved. Descriptive statistics and multivariate logistic regressions were performed. Among the 1,914 individuals with no or low intention of getting vaccinated in Fall 2021 (Period 1), 1,476 (77%) reported having received at least two doses in the Winter 2023 (Period 2). Not believing in conspiracy theory (OR = 2.08, 95% CI: 1.65-2.64), being worried about catching COVID-19 (OR = 2.12, 95% CI: 1.65-2.73) and not living in a rural area (ORs of other areas are 2.27, 95% CI: 1.58-3.28; 1.66, 95% CI: 1.23-2.26; 1.82 95% CI: 1.23-2.73) were the three main factors associated with being vaccinated at Period 2. Among the 11,117 individuals not hesitant at Period 1, 1,335 (12%) became hesitant at Period 2. The three main factors significantly associated with becoming vaccine hesitant were the adherence to conspiracy theories (OR = 2.28, 95% CI: 1.95-2.66), being a female (OR = 1.67, 95% CI: 1.48-1.90) and being younger than 65 years old (the ORs for 18-34, 35-49, and 50-64 compared with 65 and over are 2.82, 95% CI: 2.32-3.44; 2.39, 95% CI: 2.00-2.86 and 1.82, 95% CI: 1.55-2.15 respectively). As the pandemic is over, monitoring the evolution of vaccine attitudes and uptake will be important.